Interplay of pulse duration, peak intensity, and particle size in laser-driven electron emission from silica nanospheres - Powell, Jeffrey A.; Summers, Adam M.; Liu, Qingcao; Robatjazi, Seyyed Javad; Rupp, Philipp; Stierle, Johannes; Trallero-Herrero, Carlos; Kling, Matthias F.; Rudenko, Artem (My University, 2019)
We present the results of a systematic study of photoelectron emission from isolated dielectric nanoparticles (SiO2) irradiated by intense 25 fs, 780 nm linearly polarized laser pulses as a function of particle size (20 nm to 750 nm in diameter) and laser intensity. We also introduce an experimental technique to reduce the effects of focal volume averaging. The highest photoelectron energies show a strong size dependence, increasing by a factor of six over the range of particles sizes studied at a fixed intensity. For smaller particle sizes (up to 200 nm), our findings agree well with earlier results obtained with few-cycle, ∼4 fs pulses. For large nanoparticles, which exhibit stronger near-field localization due to field-propagation effects, we observe the emission of much more energetic electrons, reaching energies up to ∼200 times the ponderomotive energy. This strong deviation in maximum photoelectron energy is attributed to the increase in ionization and charge interaction for many-cycle pulses at similar intensities.